The Nexus between Financial Development and Carbon Emission in OIC Countries - Mohammad Zen Nasrudin Fajri; Ikhsanul Amal; Abdul Fareed Delawari; Ahmad Suminto (University of Darussalam Gontor, 2024)
Economic activities are important factors for the development of countries. However, many countries give too much importance to the economy without paying attention to the country's environment as a result of ongoing economic activities, such as industrial, electricity production, transportation, and commercial and residential which can cause environmental degradation with the spread of CO2 carbon dioxide emissions. The growth of a financial sector that supports those economic activities is considered the driver of carbon emissions at the macro level. However, Islam teaches Muslims to avoid corruption on earth including those leading to the rise in carbon emissions. This makes Muslim-majority countries have better concern in dealing with carbon emissions. This study aims to analyze the influences of financial institution index (FII) and financial market index (FII) on carbon dioxide emissions in the Organization of Islamic Cooperation member nations. Using the GMM estimator for a panel dataset of 36 countries between 2000 and 2021, this study unravels that the FII significantly increased carbon emissions in OIC countries. In reverse, FMI contributed to the reduction of carbon emissions in OIC countries. This paper recommends the government set regulations for banking sectors to improve eco-friendly credits for the private sector. It is also recommended that the government enrich the issuance of green securities and strengthen the financial market because it is effective in minimizing carbon emissions.